2008
DOI: 10.1371/journal.ppat.1000018
|View full text |Cite
|
Sign up to set email alerts
|

Viral Control of Mitochondrial Apoptosis

Abstract: Throughout the process of pathogen–host co-evolution, viruses have developed a battery of distinct strategies to overcome biochemical and immunological defenses of the host. Thus, viruses have acquired the capacity to subvert host cell apoptosis, control inflammatory responses, and evade immune reactions. Since the elimination of infected cells via programmed cell death is one of the most ancestral defense mechanisms against infection, disabling host cell apoptosis might represent an almost obligate step in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
385
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(390 citation statements)
references
References 99 publications
(142 reference statements)
4
385
0
1
Order By: Relevance
“…As viruses have developed sophisticated machineries to evade apoptotic cell death and interfere with ER stress and autophagy responses for their survival, 102,103 ICD may have played an essential role in the everlasting war between viruses and their hosts. We and other groups have found that many oncolytic viruses can induce apoptotic cell death and/or necrosis in cancer cells, 9,104,105,106 supporting their immunostimulatory potential to augment antitumor efficacy (Tables 4 and 5).…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 99%
“…As viruses have developed sophisticated machineries to evade apoptotic cell death and interfere with ER stress and autophagy responses for their survival, 102,103 ICD may have played an essential role in the everlasting war between viruses and their hosts. We and other groups have found that many oncolytic viruses can induce apoptotic cell death and/or necrosis in cancer cells, 9,104,105,106 supporting their immunostimulatory potential to augment antitumor efficacy (Tables 4 and 5).…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 99%
“…9 Owing to its central role in cell death regulation, MOMP is involved in the pathophysiology of human diseases as diverse as cancer, ischemia and viral infections. 10,11 MOMP can either be initiated at the outer mitochondrial membrane, owing to the pore-forming activity of the proapoptotic BCL-2 family members BAX and BAK, 12 or ensue the so-called "mitochondrial permeability transition" (MPT), an abrupt increase in the permeability of the inner mitochondrial Here, we reveal the important finding that the c subunit of the F O ATP synthase is required for MPT-driven mitochondrial fragmentation and cell death triggered by cytosolic calcium overload and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses, as obligatory parasites, have evolved highly specific means to hijack cellular pathways. To optimize the survival in their host, many viruses express factors that block or delay the death of infected cells, by acting notably at the mitochondrial level, thereby suppressing one of the most ancient antiviral mechanisms 4 . For neurotropic viruses, protecting infected neurons from excessive damage or death makes theoretical sense to facilitate viral spread and persistence, given the poor regenerative capacity of neurons.…”
mentioning
confidence: 99%